Comparative Effects of Event Detection Methods on the Analysis and Interpretation of Ca2+ Imaging Data - Neugornet, Austin; O’Donovan, Bernadette; Ortinski, Pavel Ivanovich (Frontiers in Neuroscience, 2021)
Calcium imaging has gained substantial popularity as a tool to profile activity of multiple simultaneously active cells at high spatiotemporal resolution. Among the diverse approaches to processing of Ca2+imaging data is an often subjective decision of how to quantify baseline fluorescence or F0. We examine the effect of popular F0 determination methods on interpretation of neuronal and astrocyte activity in a single data set of rats trained to self-administer intravenous infusions of cocaine and compare them to an F0-independent wavelet ridgewalking event detection approach. We find that the choice of processing method has a profound impact on interpretation of wide-field imaging results. All of the dF/F0 thresholding methods tended to introduce spurious events and fragment individual transients, leading to smaller calculated event durations and larger event frequencies. Analysis of simulated data sets confirmed these observations and indicated substantial inter-method variability as to events classified as significant. Additionally, most dF/F0 methods on their own were unable to adequately account for bleaching of fluorescence, although the F0 smooth approach and the wavelet ridgewalking algorithm both did so. In general, choice of processing method led to dramatically different quantitative and sometimes opposing qualitative interpretations of the effects of cocaine self-administration both at the level of individual cells and at the level of cell networks. Significantly different distributions of event duration, amplitude, frequency, and network measures were found across the majority of dF/F0 approaches. The wavelet ridgewalking algorithm broadly outperformed dF/F0-based methods for both neuron and astrocyte recordings. These results indicate the need for heightened awareness of limitations and tendencies associated with decisions to use particular Ca2+ image processing pipelines. Both quantification and interpretation of effects of experimental manipulations are strongly sensitive to such decisions.